Prevalence, molecular characterization, and histopathological impact of Trichomonas gallinae in domestic pigeons from Northeastern Egypt - Al-Shaimaa M. Sadek; Doaa S. Farghaly; Tasneme A. Ghazy (Scientific Reports)
Abstract Trichomonas gallinae (T. gallinae) is a single-celled flagellate protozoan that causes trichomoniasis, a serious and widespread infectious disease primarily affecting Columbiformes. This study investigated the prevalence, molecular characterization, and histopathological effects of T. gallinae in domestic pigeons (Columba livia domestica) from different environments and regions in Egypt. A total of 685 pigeons were examined from markets, dovecotes, and houses across Cairo, Giza, and Qalubyya Governorates from February 2022 to November 2024. Microscopic examination confirmed an infection in 533 pigeons, yielding an overall infection rate of 77.8%. Markets exhibited the highest prevalence (91.8%), followed by dovecotes (72.1%) and houses (58.4%). Regionally, Cairo recorded the highest infection rate (80.7%), followed by Giza (76.0%) and Qalubyya (76.0%). Seasonal variation indicated that summer accounted for the highest number of cases (48.2%), while winter had the lowest (11.4%). Age distribution revealed a strong predominance of squabs (70.7%) compared to adults (29.3%), and gender analysis showed a significantly higher prevalence in females (83.4%) than in males (16.6%). Histopathological examination of oropharyngeal mucosa, proventriculus, and gizzard showed distinct pathological changes, including severe necrosis, caseation, and granulomatous tissue reactions, which are pathognomonic for T. gallinae infection. Molecular analysis confirmed the presence of T. gallinae, with PCR amplification of the ITS1/5.8S/ITS2 gene revealing two novel strains, were deposited in GenBank with accession numbers (OR498119) and (OR498120). These strains exhibited high nucleotide sequence identity with isolates from China, Germany, and Spain, indicating a high degree of genetic conservation and a widespread global distribution of T. gallinae. These findings highlight the widespread prevalence of T. gallinae in domestic pigeons, particularly in urban and commercial environments, with seasonal, age, and gender-related variations influencing infection rates. The detection of novel genetic variants and severe tissue damage emphasizes the need for enhanced surveillance, control measures, and further research on the pathogenicity and epidemiology of T. gallinae in pigeons and potential spillovers to other avian hosts.